Perbandingan Induction Hardening dengan Flame Hardening pada Sifat Fisik Baja ST 60 - Iswanto Iswanto; Edi Widodo; Ali Akbar; Angga Kharisma Putra (Mekanika: Majalah Ilmiah Mekanika, 2020)
This study will discuss the comparison between induction hardening with flame hardening in ST 60 steel in terms of tensile strength and microstructure. The induction hardening machine is designed and made by itself with the maximum heat generated reaching 650 °C. While the flame hardening machine uses an acetylene welding machine. After heating the specimen to 650 °C, it is then cooled using water. Each heating process uses three specimens for tensile testing and microstructure testing. From the tensile test results obtained that, ST 60 steel with induction hardening has a greater tensile strength compared to flame hardening. ST 60 steels which experienced induction hardening treatment also had higher strain compared to ST 60 steels which experienced flame hardening treatments.